Fungsi Historis dalam Caption Instagram Vania Winola (Kajian Pragmatik Siber) - Nadhifah, Elok; Firmansyah, M. Bayu (Multiverse: Open Multidisciplinary Journal, 2023)
This research aims to determine the historical function of cyber pragmatics in Vania Winola's Instagram captions so that followers on her social media understand the meaning of the written in the captions. Caption is short text used to accompany an image which occurs below the upload. Cyber ??pragmatics is a branch of pragmatics that studies the meaning of speech in certain situations on social media. Therefore, this research was conducted to describe the function of cyber pragmatics in Vania Winola's Instagram captions. This research uses a cyber pragmatics approach using virtual ethnographic research methods. The research results that researchers have found are the historical function of cyber pragmatics in Vania Winola's Instagram captions. The research results have found that there are four pragmatic historical functions in Vania Winola's Instagram captions. The four functions of cyber pragmatics found in Vania Winola's Instagram caption include social, social , cultural and situational function.